Genetic variation of Bactericera cockerelli Šulc. (Hemiptera: Triozidae) suggests new haplotype in México - Beltrán-Beache, Mariana; Delgado-Ortíz, Juan Carlos; Ochoa-Fuentes, Yisa María; Cerna Chávez, Ernesto (Revista Colombiana de Entomología, 2022)
A new genetic variation and potential new haplotype of Bactericera cockerelli was identified based on the analysis of the mitochondrial region Cytochrome Oxidase subunit I of two populations from greenhouses in Villa Unión, Durango and Saltillo, Coahuila, Mexico. A variation was found in the base 247 of a 500 bp amplified of the mtCOI gene, this change implies the substitution of an adenine (A) to a Guanine (G), this mutation was detected in the insects collect from greenhouses and in their progeny obtained under laboratory conditions. This genetic variant has a great potential to be a new haplotype of B. cockerelli, therefore, it was designated Mexico Haplotype 1 (MXH1) with GenBank accession number KX130767. A total of ten insects from the original collection and then from laboratory cages were evaluated for Lso infection and all tested negative.